EVIDENCE-BASED POLICY: DATA’S USE IN SUPPORTING PUBLIC POLICY PROCESS - Yuliani, Isnaeni; Larasati, Endang; Kismartini, Kismartini; Yuningsih, Tri (Interdisciplinary Social Studies, 2022)
Bureaucratic reform became the backbone in changing the life of the nation and state. Through bureaucratic reform, arrangements are carried out on the system of government administration to make it more effective and efficient. One of the important bureaucratic reform agendas to realize is improving the quality of policies. Therefore, through this article, the author aims to provide an overview of the meaning of data / evidence in the public policy process. The writing of this article uses the literature review method, namely by utilizing secondary data or sources in the form of journals, books, documentation, the internet and various libraries that are relevant to the issues and topics of this article. The researcher concluded that the contribution of the EBP approach in the bureaucracy and policy of public institutions in each policy cycle can be a breakthrough in the birth of innovative policies. The use of research data is an important aspect in the success of government bureaucratic policies. Moreover, superior research as a source of data can identify problems more precisely and help governments design the most effective and innovative policy options.